Distribution and Frequency of ABO and Rhesus blood groups among donors at Chughtai Institute of Pathology, Lahore - Javeria Ghafoor, Muhammad Faisal Aslam, Khadeeja Khan, Muhammad Immran, Nimrah Ishaque, Ashja Saleem, Maheen Rana (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To assess the demographic background of blood donors in a referral institution located in Lahore, as well as the distribution of blood groups among those who donate blood. Additionally, the study will investigate the distribution of blood groups among those who donate blood. Study design: A cross-sectional study Place of Study: Chughtai Institute of Pathology, Lahore Study duration: March to June 2023 Results: Among the participants, blood group O was most common 202(49.26%), followed by A 110(27.1%), B 82(20%) and AB 15(3.65%). Blood group O was most common. Blood group O was the least common among participants. The least common blood group was AB, with 3.65% of male participants and 1.7% of female participants. A statistical analysis found no significant difference between gender and blood type (χ2 = 2.9932, P value =0.912). All blood groups except AB had Rh-negative antigens. A comparison of blood types found no changes in RH (χ2 = 2.112, P value = 0.698). Conclusion: For the functioning of a national health service, it is crucial to possess current information on the prevalence of blood types in various local settings. Currently, there is a lack of information on this important subject. Our research provides detailed information on the blood type and demographic characteristics of donors. Additional research and mobilisation are needed nationwide to adhere to the World Health Organization’s suggestions regarding voluntary blood donation. Keywords: Rhesus factor, ABO, blood donation, and transfusion medicine